(untitled) (Balneo and PRM Research Journal, 2022)
Abstract Background: Considering the increasing number of students that are medically exempt from physical education classes, it is imperative to find solutions that are centred on their needs. Purpose: To design a quiz app that can solve the problem of assessing exempt students and help their active and conscious integration and participation in the physical education class. Materials and method: Before designing and writing the application, a preliminary study was carried out based on a questionnaire distributed on the Google Forms platform to 84 secondary school teachers of physical education, in the counties of Galati, Braila, Buzau and Tulcea. The questions were structured so as to provide us with data about the actual working time in the lesson of a medically exempt pupil, his/her involvement or non-involvement in the subject, the distribution of working time on class segments, the provisions of the education law in relation to the exemption from effort, etc. Our contribution to this research consists in a quiz-type application, unique at the national level, which can be successfully implemented in the physical education class for medically-exempt students. During the construction of the application, the content of the current school curriculum for grades V-VIII was included into 160 questions for each content area, with multiple-choice answers and images processed according to the content in the curriculum. The application can be accessed by the exempt student regardless of his/her diagnosis, depending on the grade level, subject taught and topic of interest. The app provides an evaluation after accessing the session and contains a folder for information purposes only. Results: the questionnaire offered relevant data on the issue of integrating the medically-exempt student in the physical education class, showing that: the medically-exempt student participates in the class between 0 and 5 minutes (50% of teachers) and between 5 and 10 minutes (38% of teachers); the medically-exempt student participates only in the first segment (44% of teachers) - 22% answered that in the first and last segments of the lesson, which means that, if we approximate the time allocated to the two segments, the student does not exceed 5-8 minutes of active participation; 56% of the teachers interviewed state that students do not participate actively and consciously in the physical education class, and 94% consider that other methods of stimulating interest are needed for those who are exempt; 48% of the teachers confirm that students may have temporary exemptions, which reinforces the idea that we must find solutions so that during the period of medical exemption, the student be at least interested in acquiring the theoretical knowledge that will fundamentally help him/her when s/he becomes fit for making effort. Conclusion: The implementation of the quiz application among students exempt from physical effort in the physical education class stimulates the students’ interest to access the content of the program, makes them participate actively and consciously thanks to the facilities of the application through the possibility of self-assessment in real-time, and ensures the acquisition of theoretical knowledge through the possibility of evaluation on work sessions in real-time.